A voz baudelairiana em Fleurs de Ténèbres de Villiers de L’Isle-Adam - Domingos, Norma [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Este estudo tem o objetivo de apresentar uma análise do conto “Fleurs de Ténèbres” publicado na obra Contes cruels (1883) de Villiers de l’Isle-Adam (1838-1889). O trabalho visa, ainda, de forma particular, destacar elementos que permitem apontar relações de aproximação entre o conto villieriano e os poemas em prosa “La corde” e “Le tir et le cimetière” de Charles Baudelaire. Com efeito, a influência baudelairiana na escritura de Villiers de l’Isle-Adam diz respeito tanto aos procedimentos estilísticos quanto ao idealismo filosófico.

The purpose of this study is to present an analysis of the short story Fleurs de Ténèbres, published in Contes cruels (1883) by Villiers de l’Isle-Adam (1839-1889). It pays special attention to some of the features of the short story that allow a comparison with Baudelaire’s prose poems La Corde and Le tir et le cimetière. In fact, Baudelaire’s influence in Villiers de l’Ísle-Adam’s writing is perceived in terms of stylistic procedures and philosophical idealism.
The Baudelaire’s voice on the short story Fleurs de Ténèbres by Villiers de L’Isle-Adam
Keywords: Villiers de l’Isle-Adam; Short story; Prose poem; Fleurs de Ténèbres; Contes Cruels; Charles Baudelaire; Conto; Poema em prosa